Entire solutions of a public goods game model. Issue 8 (24th May 2022) - Wang, Lina; Zhang, Yinli; Wu, Yanxia
Abstract : This paper is concerned with the entire solutions defined in the whole space and for all time t ∈ R of a public good game model. The existence of the entire solutions is proved by super- and sub-solution method. Traveling fronts with possibly different wave speeds are used to construct the super- and sub-solutions, in particular, the traveling fronts of a variant of KPP equation are used to derive the t < 0 part of the super solutions.